2013
DOI: 10.1016/j.jss.2012.10.237
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Involvement in Immunohistochemistry-Based Molecular Classifications of Breast Cancer

Abstract: Background-Prognosis and treatment options differ for each molecular subtype of breast cancer, but risk of regional lymph node (LN) metastasis for each subtype has not been wellstudied. Since LN status is the most important predictor for prognosis, the aim of this study is to investigate the propensity for LN metastasis in each of the five breast cancer molecular subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(27 reference statements)
1
3
1
Order By: Relevance
“…In general, the LN status presents an important prognostic factor in breast cancer [21]; however, recent findings and results of our study indicate that LN metastases are generally less prevalent in luminal-A tumors than in the more aggressive subtypes of disease [20][21][22][23][24][25][26]. Rather, retrospective studies indicate that luminal-A tumors show the highest propensity to metastasize to bones, mainly when compared with the basal subtype of breast cancer [23,26,27].…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In general, the LN status presents an important prognostic factor in breast cancer [21]; however, recent findings and results of our study indicate that LN metastases are generally less prevalent in luminal-A tumors than in the more aggressive subtypes of disease [20][21][22][23][24][25][26]. Rather, retrospective studies indicate that luminal-A tumors show the highest propensity to metastasize to bones, mainly when compared with the basal subtype of breast cancer [23,26,27].…”
Section: Discussioncontrasting
confidence: 54%
“…In general, the frequency of patients with LN metastasis is lower in the luminal-A subtype than in other disease subtypes. This is particularly so when luminal-A tumors are compared with the luminal-B subtype that shares several molecular characteristics with it [20][21][22][23][24][25][26]. In contrast, bone metastases are prevalent in luminal-A patients more than in other subtypes, and bones are the preferred metastatic site in this subtype of disease [23,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, in research conducted by Howland, Driver and Chao, it was found that HER-2 numbers were more dominant than others. While in a study conducted by He, Wu, Lin in 2015, the same characteristics were also found in this study, namely ER/PR, TNBC, and HER-2 [12], [13].…”
Section: Discussionsupporting
confidence: 87%
“…The incidence of LNM was more presented in the larger tumor. Women with a tumor size >2 cm had a significantly higher risk of LN metastasis than those with tumor ≤2 cm (27). Race also had a significant influence on LNM.…”
Section: Discussionmentioning
confidence: 91%